2020
DOI: 10.3390/su12219192
|View full text |Cite
|
Sign up to set email alerts
|

How Climate Variables Influence the Spread of SARS-CoV-19 in the United States

Abstract: During the 2020 Coronavirus pandemic, several scientific types of research investigated the causes of high transmissibility and deaths caused by SARS-CoV-2. Among the spreading factors of the disease, it is known that there is an association between temperature and infected people. However, the studies that identified this phenomenon explored an association relationship, which is weaker and does not allow the identification of which variable would be the cause. This study aimed to analyze the impact of tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As can be seen in Figure 2, specific past day q obtained similar p-values corresponding to the six models. Adjacent q values, such as (12,13,14) or (19,20,21), were also located in a similar range. Compared to the Korean model in Figure 3, p-values of the Chinese model in the past days were less concentrated but still continuous and coherent along past days in a global vision.…”
Section: Stability Of Coefficientsmentioning
confidence: 84%
See 1 more Smart Citation
“…As can be seen in Figure 2, specific past day q obtained similar p-values corresponding to the six models. Adjacent q values, such as (12,13,14) or (19,20,21), were also located in a similar range. Compared to the Korean model in Figure 3, p-values of the Chinese model in the past days were less concentrated but still continuous and coherent along past days in a global vision.…”
Section: Stability Of Coefficientsmentioning
confidence: 84%
“…Furthermore, Hsieh et al [14] found that the volatility of stock prices increased substantially during crisis periods (e.g., the SARS outbreak, the 2002 anti-terror war, and the Enron scandal). To date, the humanitarian COVID-19 crisis has lasted for one year, and no one knows what the world economy will look like in 3 or 6 months [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…An increase in temperature caused a decrease in the number of infected cases. Meanwhile, a decrease in temperature after the temperature shock was associated with an increase in the number of cases, which tended to zero overall[91].…”
mentioning
confidence: 98%